2010
DOI: 10.1177/0886260510383033
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of World Assumptions on the Relationship Between Trauma Exposure and Depression

Abstract: The association between trauma exposure and mental health-related challenges such as depression are well documented in the research literature. The assumptive world theory was used to explore this relationship in 97 female survivors of intimate partner violence (IPV). Participants completed self-report questionnaires that assessed trauma history, world assumptions, and depression severity. Regression analyses revealed that diminished world assumptions mediate the relationship between trauma exposure and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 43 publications
(43 reference statements)
4
71
2
3
Order By: Relevance
“…This means that previously established cognitive schemata may be rejected as a result of experienced trauma or they can be confirmed and reinforced. The persistence of strong, rigid beliefs (both negative and positive) can accompany depression, fear, regret and other negative outcomes resulting from experienced trauma [12].…”
Section: Core Beliefs and Symptoms Of Posttraumatic Stress Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…This means that previously established cognitive schemata may be rejected as a result of experienced trauma or they can be confirmed and reinforced. The persistence of strong, rigid beliefs (both negative and positive) can accompany depression, fear, regret and other negative outcomes resulting from experienced trauma [12].…”
Section: Core Beliefs and Symptoms Of Posttraumatic Stress Disordermentioning
confidence: 99%
“…Oznacza to, że wcześniej posiadane schematy poznawcze w wyniku doznanej traumy mogą ulec odrzuceniu, ale mogą także zostać potwierdzone i usztywnione. Utrzymywanie się silnych, sztywnych przekonań (zarówno negatywnych, jak i pozytywnych) współwystępuje z objawami depresji, lęku, żalu oraz innymi negatywnymi następstwami wynikającymi z doświadczonej traumy [12].…”
Section: Podstawowe Przekonania a Objawy Stresu Pourazowegounclassified
“…According to the assumptive world theory, individuals hold some core assumptions about the world and self, such as, belief about benevolence of the world, belief about justice in the world, and belief in self-worth [23][24][25]. Belief about the world's benevolence refers to the extent to which the individual interprets the intention/disposition of the surrounding world as benign or malevolent.…”
Section: Assumptive World Theorymentioning
confidence: 99%
“…People exposed to trauma tend to have a weak belief in a just world [23]. Previous studies found that people with weak belief in a just world tend to report higher perceptions of discrimination while those with a strong belief in a just world tend to report minimal perceptions of discrimination [47][48][49][50][51][52].…”
Section: Assumptive World Theorymentioning
confidence: 99%
See 1 more Smart Citation